2008 IEEE International Conference on Software Maintenance 2008
DOI: 10.1109/icsm.2008.4658071
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of clones on changeability

Abstract: To prioritize software maintenance activities, it is important to identify which programming flaws impact most on an application's evolution. Recent empirical studies on such a flaw, code clones, have focused on one of the arguments to consider clones harmful, namely, that related clones are not updated consistently. We believe that a wider notion is needed to assess the effect of cloning on evolution. This paper compares measures of the maintenance effort on methods with clones against those without. Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 20 publications
1
64
0
Order By: Relevance
“…After that, they observed that clones influenced the maintenance effort by analyzing the effect of clones to changeability. However, they could not find systematic relation between them [159]. Rahman et al empirically validated the general negative characteristics of clones [112].…”
Section: To Empirically Validate Novel Ideas and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, they observed that clones influenced the maintenance effort by analyzing the effect of clones to changeability. However, they could not find systematic relation between them [159]. Rahman et al empirically validated the general negative characteristics of clones [112].…”
Section: To Empirically Validate Novel Ideas and Techniquesmentioning
confidence: 99%
“…Decision tree has been used to predict developers' contribution in [145]. In [65], SVM has been applied for the bug triage and in [147], association rule mining has refactoring [72], [73] API-change [74], [75], [77], [80], [81] change patterns [83]- [88], [90], [160] team-activity developer's contribution [55], [91], [93], [94], [154] experties of developers [96], [97], [149] tool support [98], [99], [128], [151] helpful information [100] comprehension visualization [101], [102], [156] identifiers [104], [105], [153] recording operations [106] validation metrics [45], [107], [157] tool [108] clones [109]- [112], [150], [159] bug [113], [114] development& evolution development [118]- [120] evolution …”
Section: Data Mining Algorithmsmentioning
confidence: 99%
“…Deligiannis et al [14] conducted an observational study where four participants evaluated two systems, one compliant and one non-compliant to the principle of avoiding God classes, and concluded that familiarity with the application domain plays an important role when judging negative effects on completeness, correctness and consistency during comprehension tasks. Lozano and Wermelinger [15] compared the maintenance effort of methods during periods when they did not contained a clone and when they did contained a clone. They found that there was no increase in the maintenance effort in 50% of the cases.…”
Section: Related Workmentioning
confidence: 99%
“…Find the origin of methods All methods that seem new at each commit transaction are compared against all methods that seem deleted in the same commit transaction in order to detect renamings, or movement of methods to other classes or packages (see [13] …”
Section: B For Each Commit Transactionmentioning
confidence: 99%
“…In previous work we measured changes and co-changes of methods while cloned vs. while not cloned [15], we compared the ease to change cloned methods vs. not-cloned-methods [13], and the relation between method characteristics and their ease to change [14]. Our previous work tried to find trends on the effect of clones in methods using measurements that depended on the periods cloned and not cloned of each method analyzed.…”
Section: Introductionmentioning
confidence: 99%